Efficacy of green tea extract on Staphylococcus aureus and Klebsiella pneumonia of raw chevon - Biswas, S; Islam, MS; Sarker, T; Islam, SS; Meem, FT; S Hassan; Fariha, S (Meat Research, 2023)
The efficacy of green tea extract with different strengths on selective microorganisms of raw chevon was investigated in this study. The experiment was conducted using completely randomized design (CRD) six treatments (T0 =0 ml of green tea; T1 =1 ml of green tea; T2 =2 ml of green tea; T3 =3 ml of green tea; T4 =4 ml of green tea and T5=5 ml of green tea) having three replications. Drop plate method was used for analyzing antimicrobial activity in this experiment. The outcome illustrated a declining microbial population in samples while incorporating green tea with colony-forming units steadily reducing from T0 to T5. There was a significant effect (p<0.0001) of green tea on the number of E. coli and Staphylococcus epidermidis. The minimum and maximum population of TVC of E. coli, in the treated sample were 6×105 CFU/ml in T5 and 45×105 CFU/ml in T0 respectively while for Staphylococcus epidermidis, it was 4×105 CFU/ml in T5 and 10×105 CFU/ml in T0 respectively. Green tea extracts showed equal growth suppression and extremely significant differences (p<0.0001) in their antimicrobial activity against both E. coli and Staphylococcus epidermidis. Given the results, it is possible to draw the conclusion that adding green tea extract at a level of 5 ml to raw chevon will diminish its microbial population. For Staphylococcus aureus and Klebsiella pneumonia were significant reduction (p<0.0001) of the microbes among samples treated with green tea extracts.